International human rights - Donnelly, Jack. (Boulder, CO : Westview Press, 2013)
Studies the ways in which states and other international actors have addressed human rights since the end of World War II. This textbook features substantial attention to the domestic politics of human rights, as well as an extensive emphasis on theory. The fourth edition is substantially rewritten and reorganized to enhance usability, and new material is added to bring the text up to date. Most notably, the sections covering multilateral, bilateral, and transnational action have been broken into seven short chapters, which encourage comparisons within and across types of action and historical cases. New case studies provide context and points of comparison, including a new examination of the contemporary international reactions to human rights violations in China now that the country has become a great power. Additionally, nine "problems" have been added to the text, which along with the chapter-ending discussion questions, frame alternative interpretations, highlight controversies, and ultimately aim to provoke further thought and discussion amongst readers.
Part 1: Introduction and theory. Human rights as an issue in world politics -- Theories of human rights -- The relative universality of human rights -- The domestic politics of human rights: dirty wars in the southern cone -- Part 2: Multilateral, bilateral, and transnational action. Global multilateral mechanisms -- Regional human rights regimes -- Assessing multilateral mechanisms -- Human rights and American foreign policy: Cold War-era cases and comparisons -- Human rights and foreign policy -- Transnational human rights advocacy -- Comparing international actors and evaluating international action -- Part 3: Post-Cold War issues and cases. Responding to human rights violations in China: Tiananmen and after -- Humanitarian intervention against genocide -- Globalization, the state, and human rights -- (Anti)terrorism and human rights.
Includes bibliographical references and index.
Keywords: Human rights; International relations; Human rights; International relations; Derechos humanos; Relaciones internacionales